Motherhood, Psychological Risks, and Resources in Relation to Alcohol Use Disorder: Are There Differences between Black and White Women?. (19th April 2014) - Balan, Sundari; Widner, Gregory; Chen, Hsing-Jung; Hudson, Darrell; Gehlert, Sarah; Kato Price, Rumi
Abstract : Rates of alcohol use disorders (AUD) are generally low among women who have ever had children (mothers) compared to women who have never had children (nonmothers), presenting a motherhood advantage . It is unclear if this advantage accrues to "Black" and "White" women alike. Using National Epidemiological Survey on Alcohol and Related Conditions (NESARC) wave 2 cross-sectional data that is rich in alcohol use and psychological measures, we examined the following: (a) if motherhood is protective for past-year AUD among Black (N = 4, 133 ) and White women (N = 11, 017 ); (b) potential explanatory psychological mechanisms; and (c) the role of race. Prevalence of a past-year DSM-IV AUD was lower among White mothers compared to White nonmothers, but this same advantage was not observed for Black women. Perceived stress was a risk for all women, but race-ethnic segregated social networks and perceived discrimination predicted current AUD for Black mothers. Unlike White mothers, current psychological factors but not family history of alcohol problems predicted AUD for Black mothers. Future prospective studies should address the mechanisms by which race, motherhood, and psychological factors interactively affect AUD in women.